TRADISI MASYARAKAT JAWA DALAM PERTUMBUHAN PADI WIWITAN DI DESA SUMBERAGUNG KEC. PLUMPANG KAB. TUBAN - Supri yanto; Emi Fahrudi; Kumaidi Kumaidi (ASWALALITA: Journal of Da'wah Management, 2023)
ABSTRACT The wiwitan tradition is a slametan tradition before the rice harvest arrives which is intended for the ancestors or ancestors. This ritual is carried out as a form of gratitude and thanks to the earth as a sikep, and Dewi Sri (Goddess of Rice) whom they believe is the goddess who grows rice. As well as an expression of the people's gratitude to the creator for giving such abundant results. This study aims to explain the meaning, purpose and meaning of the wiwitan tradition and understand the influence of modernization on the shift in the wiwitan tradition in Sumberagung Village, Plumpang District, Tuban Regency, and what factors distinguish the ancient wiwitan tradition from today. The method used in this study is a qualitative method, namely research by collecting various information or findings that cannot be obtained using statistical procedures or quantification methods.